pragmatic functions in Arabic grammar (Journal of Misan Researches, 2024)
This research deals the pragmatic functions proposed within the framework of the theory of functional grammar, and rooting them in the theory of Arabic grammar. It highlights the opinions of Arabic scholars and their understanding of the pragmatic aspect during grammatical theorizing. The research took the approach of comparing the two theories, regarding the concept of pragmatic functions.